ANALYZING THE EFFECTIVENESS OF BLENDED LEARNING MODELS FOR ENGLISH LANGUAGE ACQUISITION IN HIGHER EDUCATION - Kusumastiti, Weka (Jurnal Review Pendidikan dan Pengajaran, 2024)
This research aims to analyze the effectiveness of blended learning models in English language acquisition in higher education. Focusing on the diversity of language proficiency and learning styles among students, the study employs a literature review method to identify the strengths, challenges, and potential solutions of implementing blended learning models. The results of the literature analysis indicate that this model successfully enhances students' English language skills through a more contextual and interactive approach. However, challenges such as student resistance and lack of faculty support also emerge. Therefore, the study offers recommendations to address these constraints, including faculty training in implementing educational technology. In conclusion, the integration of online and face-to-face approaches can positively contribute to English language acquisition in higher education, with a caveat that special attention is needed for social, technological, and faculty support aspects.